Structural and Optical Characteristics of Carboxymethylcellulose / Polyacrylic Acid Polymer Blend - Yaqoob M. Jawad; Mahasin F. Hadi Al- Kadhemy (Journal of Kufa-Physics, 2021)
The blending technology makes it possible to rebuild high molecular weights of partial polymers, thus to improve the product performance together with improvement of specific properties. Pure Carboxymethylcellulose (CMC) film and CMC (80%) doped Polyacrylic Acid (PAA) (20%) films were prepared by using a solution casting method. The influence of PAA polymer addition on the structural and optical properties of CMC polymer was investigated systematically. From X-ray diffraction patterns, adding a polymer PAA to a polymer CMC can lead to the appearance of peaks in polymer blend. FESEM image for CMC/ PAA film showed the formation of small spherical grains for PAA into CMC that insured the existence of some peaks in XRD pattern of PAA in CMC film which means the improvement of the microstructure of the polymer matrix. No chemical interactions were observed between CMC and PAA polymers from results of FTIR spectrum, so that incorporation of PAA into CMC polymer will results physical reaction only. The results of the UV spectrum have shown that the absorbance, absorption coefficient, extinction coefficient, refractive index, real and imaginary dielectric constants were increased in blend polymer compared with the pure polymer. The energy gap and transmittance of blend polymer compared with the pure polymer were reduced.